Borderline ovarian tumors: a review of its biology, molecular profile, and management - Bonadio, Renata Colombo; de Siqueira Santos, Ana Gabriela; Estevez-Diz, Maria Del Pilar (Brazilian Journal of Oncology, 2024)
Borderline ovarian tumors typically exhibit indolent behavior and boast a favorable prognosis; however, a subset of patients experiences disease recurrence and progression to low-grade ovarian carcinoma. The complex biology underlying these phenomena has been illuminated through molecular analyses. KRAS and BRAF mutations have emerged as recurrent findings in borderline ovarian tumors. Specifically, KRAS mutations have been linked to a higher risk of recurrence and progression to low-grade ovarian carcinoma, while BRAF mutations seem to confer a protective effect, inducing a senescent state that mitigates the likelihood of progression. In this comprehensive review, we explore the biology and the molecular profile of borderline ovarian tumors, shedding light on recent discoveries that have enriched our comprehension. Additionally, we discuss the current state of borderline ovarian tumors management. Surgery remains the cornerstone of treatment. While cytotoxic therapies role is limited so far, molecular characterization emphasizes the imminent potential for personalized therapeutic approaches.
Keywords: Ovarian neoplasms; Rare diseases; Molecular biology